Goal-oriented therapy of coagulopathy in liver transplantation in children (literature review) - D. I. Novikov; A. Yu. Zaitsev; A. V. Filin; A. V. Metelin (Вестник анестезиологии и реаниматологии)
Introduction. Methods for correcting perioperative blood loss and hemostasis disorders in children during liver transplantation are still controversial and are largely conducted empirically by specialists. Additional difficulties are imposed by the features of a continuously growing and developing organism, as well as the following hemostasis system.The objective was to analyze modern approaches to the correction of hemostasis disorders in children in the perioperative period of liver transplantation.Materials and methods. The analysis of literary sources indexed for the period from 2000 to 2024 in the databases PubMed, Google Scholar, Cochrane MEDLINE and E-Library (for Russian authors).Results. The analysis of the literature has shown that at present, in liver transplantation in children, a personalized approach prevails in choosing the tactics of infusion – transfusion therapy and correction of developing changes in the hemostasis system. Modern approaches are aimed at the fastest possible identification of specific perioperative disorders of pro- and anticoagulant factors directly «at the patient’s bedside» and targeted correction of each specific element.Conclusion. Despite the active development and improvement of approaches to correcting perioperative hemostasis disorders during liver transplantation, improving pharmacotherapy protocols, minimizing the time to obtain laboratory data and reducing the influence of the human factor on the interpretation of results and treatment choice, the study of the hemostasis system and correction of its disorders is still very far from the final stage.